An Alveolar Bone Augmentation Technique to Improve Esthetics in Anterior Ceramic FPDs: A Clinical Report - Burak Taskonak1 and Yasar Ozkan2 (Journal of Prosthodontics, 2006)
This clinical report describes guided bone augmentation for treatment of a facial maxillary alveolar bone defect to enhance the esthetic result for an all-ceramic fixed partial denture (FPD).